Evaluation of the radon adsorption efficiency of activated carbon fiber using tetrafluoromethane. (12th January 2022) - Kotsar, Y; Nakano, Y; Takeuchi, Y; Miuchi, K
Abstract: The radioactive noble gas radon-222 ( 222 Rn) is one of the most significant background sources in various types of rare event experiments, such as direct dark matter searches, neutrinoless double-beta decay searches, and neutrino experiments. Previously, a method to measure ^222Rn concentration in purified air, argon, and xenon gases at a level of 1 mBq/m^3 was established. Since other detector media are used in these experiments, there is a potential need to expand the study for other types of gases. In this paper the performance of an 80 liter ^222Rn detector filled with tetrafluoromethane (CF_4 ) gas, which is used for a direct dark matter search experiment, NEWAGE, was measured. The calibration factor of the detector for the CF_4 gas was measured and its dependence on the absolute humidity was investigated. We also employed activated carbon fiber to evaluate its 222 Rn adsorption efficiency in CF4, which was found to be 82.7± 0.1(stat.)± 2.3(syst.)% at 0.10 MPa. For pressures lower than atmospheric pressure, we found that adsorption efficiency rises with lower pressure, and it is equal to 93.7± 0.3(stat.)± 3.9(syst.)% at 0.03 MPa.